Quantum hack isn’t ready yet. - Sparkes, Matthew (New Scientist, 2023)
For example, the widely used RSA algorithm relies on the fact that multiplying two prime numbers to generate a large encryption key is easy, while finding those original prime factors when you only have the encryption key is very difficult. News A GROUP of researchers has claimed that quantum computers can now crack the encryption we use to protect emails, bank accounts and other sensitive data. But quantum computers can exploit the unusual properties of quantum physics to speed up some calculations and will probably render current encryption techniques obsolete once the hardware is sufficiently powerful and accurate.